Morphological and Structural changes of CaxSr1-xTiO3 Powders Obtained by the Microwave-Assisted Hydrothermal Method - Souza, Agda E. [UNESP]; Santos, Gleyson T. Almeida [UNESP]; Silva, Ranilson A. [UNESP]; Moreira, Mario L.; Volanti, Diogo P. [UNESP]; Paris, Elaine C.; Teixeira, Silvio R. [UNESP]; Longo, Elson [UNESP] (Wiley-Blackwell, 2012)
CaxSr1-xTiO3 samples were synthesized by the microwave-assisted hydrothermal method. The X-ray diffraction results indicate that strontium calcium titanates powders show two crystalline structures: perovskite cubic and orthorhombic. The ultraviolet-visible spectra show that the band gap energies decrease with the Ca addition, suggesting imperfections or defects in the forbidden band of the titanates. The photoluminescence spectra show a broad band, which is usually observed at low temperatures in perovskite-type crystals. The nanoparticles show a nonuniform distribution with polyhedral morphology and spherical agglomerates, which change to faceted surfaces suggesting that the sample can reach other morphologies which ensure symmetry of lowest energy.